3D mass digitization: a milestone for archaeological documentation - Santos, Pedro; Ritz, Martin; Fuhrmann, Constanze; Fellner, Dieter (Virtual archaeology review, 2017)
In the heritage field, the demand for fast and efficient 3D digitization technologies for historic remains is increasing. Besides, 3D digitization has proved to be a promising approach to enable precise reconstructions of objects. Yet, unlike the digital acquisition of cultural goods in 2D widely used today, 3D digitization often still requires a significant investment of time and money. To make it more widely available to heritage institutions, the Competence Center for Cultural Heritage Digitization at the Fraunhofer Institute for Computer Graphics Research IGD has developed CultLab3D, the world’s first 3D mass digitization facility for collections of three-dimensional objects. CultLab3D is specifically designed to automate the entire 3D digitization process thus allowing to scan and archive objects on a large-scale. Moreover, scanning and lighting technologies are combined to capture the exact geometry, texture, and optical material properties of artefacts to produce highly accurate photo-realistic representations. The unique setup allows to shorten the time needed for digitization to several minutes per artefact instead of hours, as required by conventional 3D scanning methods.